Optimal Supervisory Architecture and Financial Integration in a Banking Union - Colliard, Jean-Edouard (Review of Finance, 2020)
Abstract Both in the USA and in the Euro area, bank supervision is the joint responsibility of local and central supervisors. I study a model in which local supervisors do not internalize as many externalities as a central supervisor. Local supervisors are more lenient, but banks also have weaker incentives to hide information from them. These two forces can make a joint supervisory architecture optimal, with more weight put on centralized supervision when cross-border externalities are larger. Conversely, more centralized supervision endogenously encourages banks to integrate more cross-border. Due to this complementarity, the economy can be trapped in a suboptimal equilibrium with either too little or too much central supervision, when a superior equilibrium would be achievable.